THE EFFECTIVENESS OF CHUNKING STRATEGY IN DEVELOPING STUDENT'S ABILITY IN STORY RETELLING - Rohmaniyah Nia; Nur Ekaningsih (Prominent, 2020)
Abstract: This research aims at finding out whether or not the use of chunking strategy is effective in developing students’ ability of story retelling to the tenth-grade students at MAN 01 Pekalongan. Quasi experimental research was applied as the method with two groups : experimental and control group. The total subject of this research was 52 students which were taken from two classes of X IPS 1 as a control group and X AGAMA 2 as an experimental group. Face and content validity were done by asking the English teacher and advisor to be expert judgements to validate the instrument by using a rubric appearance of test for face validity and its conformity by curriculum as a content validity. Inter-rater reliability in giving scores to the students’ was done to measure the reliability of the test. This research used SPSS in analysing the data of speaking test through several activities. They were pre-test before treatments, and post-test after treatments. The result of the research shows the significant difference in the story retelling ability between tenth grade students who were taught by using chunking strategy and those were not taught by using it. It can be seen in the result of mean score in the post-test of experimental class which is 89 and control class which is 83 and as a result Sig. (2-tailed) is 0.044 less than 0.050. Therefore, the null hyothesis of this study is rejected. It means that the use of chunking strategy had significantly improved the tenth-grade students story retelling ability in English teaching and learning process of the experimental class at MAN 01 Pekalongan in the academic year 2019/2020. Keywords:     chunking, teaching speaking strategy, story retelling